Conjugated Copolymers That Shouldn't Be. (8th April 2021) - Guan, Jun; Sun, Zejun; Ansari, Ramin; Liu, Yujia; Endo, Aimi; Unno, Masafumi; Ouali, Armelle; Mahbub, Shahrea; Furgal, Joseph C.; Yodsin, Nuttapon; Jungsuttiwong, Siriporn; Hashemi, Daniel; et al.
Abstract: Multiple studies have explored using cage silsesquioxanes (SQs) as backbone elements in hybrid polymers motivated by their well‐defined structures and physical and mechanical properties. As part of this general exploration, we report unexpected photophysical properties of copolymers derived from divinyl double decker (DD) SQs, [vinyl(Me)Si(O0.5 )2 ][PhSiO1.5 ]8 [(O0.5 )2 Si(Me)vinyl] (vinylDDvinyl). These copolymers exhibit strong emission red‐shifts relative to model compounds, implying unconventional conjugation, despite vinyl(Me)Si(O‐)2 siloxane bridges. In an effort to identify minimum SQ structures that do/do not offer extended conjugation, we explored Heck catalyzed co‐polymerization of vinyl‐ladder(LL)‐vinyl compounds, vinyl(Me/Ph)Si(O0.5 )2 [PhSiO1.5 ]4 (O0.5 )2 Si(Me/Ph)vinyl, with Br‐Ar‐Br. Most surprising, the resulting oligomers show 30–60 nm emission red‐shifts beyond those seen with vinylDDvinyl analogs despite lacking a true cage. Further evidence for unconventional conjugation includes apparent integer charge transfer (ICT) between LL‐co‐thiophene, bithiophene, and thienothiophene with 10 mol % F4 TCNQ, suggesting potential as p‐type doped organic/inorganic semiconductors. Abstract : Unexpected excited‐state conjugation was observed in a series of copolymers derived from ladder silsesquioxane, vinyl(Me/Ph)Si(O0.5 )2 [PhSiO1.5 ]4 (O0.5 )2 Si(Me/Ph)vinyl, which exhibited 30–60 nm red‐shifted emission relative to double‐decker derived analogues with equal or larger degrees of polymerization. Further studies hint at their potential application as semiconducting polymers.